Inadequate empirical antibiotics following debridement for orthopedic infections do not increase therapy failures - S. M. Maurer; M. S. Maurer; M. Schmid; S. Dossi; S. Dossi; L. Gautier; A. E. Boyd; M. Farshad; I. Uçkay; I. Uçkay (Journal of Bone and Joint Infection)
Introduction: Empirical antibiotics should only target the most likely pathogens if antibiotic stewardship is being heeded. However, there is a drive for broader-spectrum empirical antibiotics in orthopedic infections due to the concern of therapeutic failure if a regimen fails to target subsequently identified pathogens. Methods: Retrospective case-control study with surgically managed orthopedic infections from July 2018 to June 2024 with a minimum follow-up of 6 months. Patients were stratified by the initial empirical treatment of either accurate empirical choice or inaccurate empirical choice. Results: Of 482 infection episodes, 79 antibiotic regimens (43 broad-spectrum; 9 %) were used with a median postoperative duration of 42 d (interquartile range 19–45 d); 290 infection episodes (60 %) were correctly targeted. In 192 cases (40 %), the initial empirical choice was inaccurate, with a median switching time to a targeted treatment of 4 d. There was no difference between accurate and inaccurate empirical treatment in terms of ultimate failures (18/290 vs. 15/192; Pearson χ2 test, p=0.49), overall adverse events of therapy (15 % vs. 7 %, p=0.11), duration of hospital stay (median 9 d vs. 9 d, p=0.96), or supplementary surgical debridement (median 0 vs. 0 intervention, p=0.58). In multivariate logistic regression analysis, the duration of an inaccurate antibiotic treatment failed to alter the risk of “failures” (odds ratio 0.9, 95 % confidence interval 0.8–1.1). Conclusions: A delay in commencing targeted antibiotics does not increase the risk of a negative outcome. Narrower-spectrum empirical regimens are appropriate for clinically mild to moderate infections as a broader spectrum does not provide any clinical advantage.